2007
DOI: 10.1091/mbc.e06-12-1074
|View full text |Cite
|
Sign up to set email alerts
|

Cdc13 Telomere Capping Decreases Mec1 Association but Does Not Affect Tel1 Association with DNA Ends

Abstract: Chromosome ends, known as telomeres, have to be distinguished from DNA breaks that activate DNA damage checkpoint. Two large protein kinases, ataxia-teleangiectasia mutated (ATM) and ATM-Rad3-related (ATR), control not only checkpoint activation but also telomere length. In budding yeast, Mec1 and Tel1 correspond to ATR and ATM, respectively. Here, we show that Cdc13-dependent telomere capping attenuates Mec1 association with DNA ends. The telomeric TG repeat sequence inhibits DNA degradation and decreases Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 66 publications
5
52
1
Order By: Relevance
“…In S. cerevisiae, the mitosis entry checkpoint1 (Mec1) kinase, the ATR homolog, has a predominant role in response to DSBs. In agreement with this, S. cerevisiae cells deficient in telomerase or the ssDNA binding protein Cdc13 activate a Mec1-dependent checkpoint (Enomoto et al, 2002;IJpma and Greider, 2003;Hirano and Sugimoto, 2007).…”
Section: Introductionsupporting
confidence: 56%
“…In S. cerevisiae, the mitosis entry checkpoint1 (Mec1) kinase, the ATR homolog, has a predominant role in response to DSBs. In agreement with this, S. cerevisiae cells deficient in telomerase or the ssDNA binding protein Cdc13 activate a Mec1-dependent checkpoint (Enomoto et al, 2002;IJpma and Greider, 2003;Hirano and Sugimoto, 2007).…”
Section: Introductionsupporting
confidence: 56%
“…DNA double-strand breaks are typically resected, initially being degraded from 59 to 39 to create single-stranded 39 overhangs at the break (White and Haber 1990). However, it has been shown that when short tracts of telomere repeat sequences are placed adjacent to the DNA break site, the broken DNA end is protected from degradation (Diede and Gottschling 1999;Michelson et al 2005;Hirano and Sugimoto 2007). The presence of this telomere ''seed'' sequence also greatly stimulates the addition of new telomere repeats to the DSB (Diede and Gottschling 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this telomere ''seed'' sequence also greatly stimulates the addition of new telomere repeats to the DSB (Diede and Gottschling 1999). The ability of this de novo telomere to cap the new DNA end has been shown to be critically dependent upon Cdc13 (Diede and Gottschling 1999;Hirano and Sugimoto 2007). Since Cdc13 is proficient for telomere localization in ten1-ts strains and the mutant Ten1 RAD52 ten1D 47 6 24 2.1 6 0.8 1.0 6 0.6 1.2 6 1.0 0.6 6 0.6 rad52D ten1D 40 6 15 0.5 6 0.5 0.2 6 0.3 0.2 6 0.1 0.4 6 0.6 exo1D ten1D…”
Section: Resultsmentioning
confidence: 99%
“…Because the telomere-binding proteins Cdc13 and Rap1 stimulate de novo telomere addition at artificial sequences in S. cerevisiae (12)(13)(14)(15)43), we hypothesized that one or both of these proteins could be responsible for the enhancing activity of the Stim sequence. Although Cdc13 and Rap1 bind similar sequences, we were able to design artificial sequences that bind with great preference to one protein as measured in vitro.…”
Section: Discussionmentioning
confidence: 99%